Decolonial Dreaming in the Sauútiverse - Nedine Moonsamy (The Thinker)
There has been a recent surge in Africanfuturist anthologies, and collections like Dominion (eds. Zelda Knight and Oghenechovwe Donald Ekpeki, 2020), Africanfuturism: An Anthology (ed. Wole Talabi, 2020), Africa Risen (eds. Sheree Renée Thomas, Oghenechovwe Donald Ekpeki and Zelda Knight, 2022), and The Year’s Best African Speculative Fiction (ed. Oghenechovwe Donald Ekpeki 2021, 2022, 2023) have established African SF as a global and popular genre in its own right. Mothersound: The Sauútiverse Anthology (2023), edited by Wole Talabi, is the most recent addition to this trend, but it also works to exceed it through a method of complex, shared worldbuilding which further exploits the decolonial potential of Africanfuturism.